Info-Communication Systems Based on E-mail and SMS Technologies - Andranik E. Mkhitaryan (Изд-во НАН РА)
The features of the widespread systems for the exchange of messages in computer and cellular networks, the prerequisites for the creation of combined messaging systems using IP and GSM technologies are considered. The peculiarities of the construction of hybrid e-mail / SMS info-communication systems are considered.
Keywords: Mathematics